On the marriage of flexibility and security: lessons from the Hartz-reforms in Germany - Leschke, Janine; Schmid, Günther; Griga, Dorit (Berlin, 2006)
"In the context of the ongoing reforms on European labour markets the keyword ‘flexicurity’ is presently gaining prominence. We therefore want to explore the importance of the flexicurity-concept on the example of the German Hartzreforms. Starting from the frequently used definition as a trade-off between employers’ demands for flexibility and employees’ needs for security, different conceptualisations of flexicurity are considered, and criteria for an efficient and equitable flexicurity-nexus are developed. The German debate on flexicurity is briefly looked at. The main part of the paper is devoted to analysing four policy measures which were implemented within the Hartz-reforms: ‘Ich-AG’ allowance for newly founded businesses, ‘personnel service agencies’ (‘PSA’) to place unemployed into regular employment, ‘Mini-Jobs’ and the introduction of ‘Midi-Jobs’ which were supposed to serve as stepping stones into employment subject to social insurance contributions and ‘wage insurance’ for elderly workers. It is assessed whether the measures contribute to enhancing the components of flexibility and security and whether the measures are appropriately balanced. The analysis reveals that the measures’ quality could be improved by strengthening different components of the security dimension."